Social Networks: Models of Information Influence, Control and Confrontation - Chkhartishvili, Alexander G.; Gubanov, Dmitry A.; Novikov, Dmitry A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book surveys the well-known results and also presents a series of original results on the mathematical modeling of social networks, focusing on models of informational influence, control and confrontation. Online social networks are intended for communication, opinion exchange and information acquisition for their members, but recently, online social networks have been intensively used as the objects and means of informational control and an arena of informational confrontation. They have become a powerful informational influence tool, particularly for the manipulation of individuals, social groups and society as a whole, as well as a battlefield of information warfare (cyberwars). This book aimed at under- and postgraduate university students as well as experts in information technology and modeling of social systems and processes.
Models of influence in social networks -- Models of informational control in social networks -- Models of informational confrontation in social networks.
Keywords: Computational intelligence; Control engineering; Artificial intelligence; Computational Intelligence; Control and Systems Theory; Artificial Intelligence